PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP PERILAKU INOVATIF DAN KINERJA KARYAWAN PT. BANK NEGARA INDONESIA CABANG PEKANBARU - Rahmad Saleh Warso; Susi Hendriani; Jahrizal Jahrizal (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of work environment and job satisfaction on innovative behavior. The effect of innovative behavior on employee performance. The influence of the work environment on performance through innovative behavior. The influence of the work environment on performance through innovative behavior. In this study, the population is the population in this study are employees of PT. Bank BNI Pekanbaru Branch Office as many as 133 people. While the sample used as many as 133 people. The data used in this study were primary data and secondary data, while the data collection technique used a questionnaire. The data analysis technique used in this study is the data analysis used in this study is SEM. Work environment and job satisfaction have an effect on innovation behavior. Innovation behavior has a significant effect on employee performance. The work environment has a significant effect on employee performance through innovation behavior and job satisfaction has a significant effect on employee performance through innovation behavior